2014
DOI: 10.1155/2014/257971
|View full text |Cite
|
Sign up to set email alerts
|

HFiltering for Discrete-Time Genetic Regulatory Networks with Random Delay Described by a Markovian Chain

Abstract: This paper is concerned with theH∞filtering problem for a class of discretetime genetic regulatory networks with random delay and external disturbance. The aim is to designH∞filter to estimate the true concentrations of mRNAs and proteins based on available measurement data. By introducing an appropriate Lyapunov function, a sufficient condition is derived in terms of linear matrix inequalities (LMIs) which makes the filtering error system stochastically stable with a prescribedH∞disturbance attenuation level.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Moreover, we can get the corresponding observer gain matrices as follows: K 1 = P −1 1 W 1 = 0, K 2 = P −1 2 W 2 = 1.5571. Further, when σ(t) = τ (t) = 1, the state responses of GRN (37), observer (5) and the corresponding error system are given in Figures 1-6. V. CONCLUSIONS In this paper, the state estimation problem for a class of GRNs with time-varying delays and reaction-diffusion terms are studied.…”
Section: Illustrative Examplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, we can get the corresponding observer gain matrices as follows: K 1 = P −1 1 W 1 = 0, K 2 = P −1 2 W 2 = 1.5571. Further, when σ(t) = τ (t) = 1, the state responses of GRN (37), observer (5) and the corresponding error system are given in Figures 1-6. V. CONCLUSIONS In this paper, the state estimation problem for a class of GRNs with time-varying delays and reaction-diffusion terms are studied.…”
Section: Illustrative Examplesmentioning
confidence: 99%
“…A great amount of experimental results show that mathematical modeling of GRNs can be a powerful tool for researching the gene regulation process and discovering complex structure of a biological organism [1]- [3]. Generally, there are two basic models for GRNs: Boolean model (discrete-time model) [4], [5] and differential equation model (continuous-time model) [6]- [8]. Differential equation model describes the change rates of the concentrations of mRNAs and proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mathematical modeling of GRNs as dynamical system models provides a powerful tool for studying gene regulation processes in living organisms, models of GRNs in literature can be roughly classified into two types, i.e., the discrete model [1], [2], [26] and the continuous model [3], [4], [5], [6]. Usually, a continuous model is described by a (functional) differential equation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been well recognized that time delay is one of the main sources leading to instability and poor performance of a system [7], [8], [9]. As a result, much effort has been paid to the study of GRNs described by FDEMs, and many significant results have been reported in literature on the stability analysis, controller synthesis, filter design, and so on (see, e.g., [7], [8], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28]). …”
Section: Introductionmentioning
confidence: 99%